Peningset, srah-srahan dan midodareni/ Suwarna Pringgawidagda; penyunting, Hermawan Hastho Nugroho. - SUWARNA PRINGGAWIDAGDA, 1964-; Hermawan Hastho Nugroho (Adicita Karya Nusa, 2003)
x, 54 hlm.: ilus.; 21 cm.(3 eks)